Prevalence of Bone Density Reduction and Its Related Factors in Hemophilia Patients in South Khorasan Province in 2018: - Ehsanbakhsh, Alireza; Azarkar, Ghodsiyeh; Ziaee, Masood; Taghavieh, Ali (Galen Medical Journal, 2020)
Background: The present study aimed to determine the prevalence of bone density reduction and its associated factors in hemophilia patients in South Khorasan Province in 2018. Materials and Methods: This case-control study was conducted on all patients with hemophilia type A with medical records in Hemophilia center in South Khorasan province. A number of 57 eligible subjects who met the criteria were selected based on census method. Thereafter, 60 non-hemophilic individuals who were similar to hemophilic patients in terms of age and body mass index were selected by convenience sampling method. DXA device was used to measure bone mineral density (BMD) in two locations of femoral neck and lumbar vertebrae. Data were analyzed in SPSS software (version 19), using Chi-square, Fisher’s exact test, and independent t-test. A P-value less than 0.05 was considered statistically significant. Results: The prevalence rate of bone density reduction in spine bone in hemophilia patients was measured at 31.6% and 13.3% in non-hemophilia subjects (P=0.02); moreover, this rate in hip bone was reported as 7% and 5%, respectively (P=0.65). Relative frequency of bone density reduction in the spine and hip bone was not significantly different among hemophilia patients based on age, severity of hemophilia, vitamin D, hepatitis and smoking (P>0.05). However, a significant difference was detected in terms of body mass index (P<0.05). Conclusion: Based on the obtained results, the prevalence of bone density reduction in hemophilic patients was significantly higher, as compared to that of non-hemophilia patients. This necessitates the implementation of drastic preventive measures, prompt diagnosis, timely treatment, and appropriate therapeutic measures. [GMJ.2020;9:e1711]